A universal synthetic methodology of superhydrophobic protective film on various substrates with convenient and stable precursor. (April 2023) - Zhou, Yuqin; Liu, Enhong; Kang, Jianhai; Zhao, Shuang; Wang, Luping; Yan, Huiyu; Hu, Chenxi; Han, Jianhua
Abstract: In this study, we presented a universal and convenient method to prepare superhydrophobic film on the substrates of Al, Al alloy, indium-tin oxide (ITO), fluorine doped tin oxide (FTO) and glass slide respectively. The precursor solution of silane mixture was recovered by dissolving the pre-synthesized powders of silane in alcohol, which is easy to prepare and store, stable and portable. As expected, all of the five substrates achieved superhydrophobic properties with contact angle of more than 160° after spin-coating the above precursor on their surface. In addition, the effect of superhydrophobic film thickness on light transmittance was investigated by spin-coating different concentrations of precursor solutions on ITO substrates. There is a certain transmission enhancement effect on the wavelength range of 525–675 nm, indicating the good light transmittance of superhydrophobic film prepared by this method. Electrochemical measurements confirmed that the superhydrophobic film coated Al and its alloys possess excellent anti-corrosion properties. Highlights: A universal and convenient method to prepare superhydrophobic protective film on various substrates was presented. The precursor solution was recovered by dissolving the pre-synthesized powders in alcohol. Excellent superhydrophobic, self-cleaning and anti-corrosion properties were achieved. The superhydrophobic film possess good light transmittance in visible region.